The Project Manager “Interfaces” in a Crisis Scenario - Di Lorenzo, Daniele (European Scientific Journal, ESJ, 2021)
A crisis induces Project Managers to use, increasingly, a specific “language” that is born from the union of two dimensions, technical-operative modalities and the mindset. The goal is to properly react to the crisis, like a pandemic scenario will. This approach directly involves the usage of “triad” (Reaction-Execution-Results) and micro-goals concepts in order to maximize the effectiveness and efficiency of the Project Manager actions within time windows. Project management is one of most important discipline in a company, especially where the project is the soul of the business and the center of the employees’ dynamic. This paper focuses on the “interfaces” between project management and other company functions. It analyzes how the “language” could induce reaction behavior based on the time-constraints and micro-goal modus operandi and how the company dynamic could change its behavioral habits towards the same common company purpose: the success of projects.